The use of Trademarks and IP Rights as Company Assets – An Overview of the State of play in the Republic of North Macedonia in Relation to Global Trends - Toshevska trpchevska, Katerina; Kocev, Ljuben (WIPO & WTO, 2022)
The aim of this paper is to evaluate the importance of trademarks and intellectual property (IP) rights as company assets in general. The evaluation is performed through the analysis of the legal framework in the Republic of North Macedonia and assessment of the interface between trademarks and IP rights in general as intangible assets and company law within the country. This paper firstly analyses trademarks as IP rights, primarily through their essential functions. Afterwards, the paper assesses trademark and IP rights in general through the prism of the company law in the Republic of North Macedonia. In particular, the paper analyses the possibility of investing IP rights in companies as equity – the legal framework and the methods for valuation of the IP rights. The paper further explores methods for IP commercialisation – licensing and franchising as the most suitable and commonly used practices for trademark promotion. The final part of the paper will analyse some of the world's most successful companies and how they create value and successful brands using trademarks before addressing the situation with domestic companies, how much they invest in trademarks as a means of building a successful brand, and how much IP rights as intangible assets participate in the overall value of the companies in the Republic of North Macedonia.
Keywords: trademarks; IP rights; company law; brand value; IP commercialisation; intangible assets